Cavotricuspid isthmus ablation guided by force‐time integral – A randomized study. Issue 5 (17th March 2022) - Asvestas, Dimitrios; Sousonis, Vasileios; Kotsovolis, George; Karanikas, Stavros; Xintarakou, Anastasia; Sakadakis, Eleftherios; Rigopoulos, Angelos G.; Kalogeropoulos, Andreas S.; Vardas, Panos; Tzeis, Stylianos
Abstract: Background: Force‐time integral (FTI) is an ablation marker of lesion quality and transmurality. A target FTI of 400 gram‐seconds (gs) has been shown to improve durability of pulmonary vein isolation, following atrial fibrillation ablation. However, relevant targets for cavotricuspid isthmus (CTI) ablation are lacking. Hypothesis: We sought to investigate whether CTI ablation with 600 gs FTI lesions is associated with reduced rate of transisthmus conduction recovery compared to 400 gs lesions. Methods: Fifty patients with CTI‐dependent flutter were randomized to ablation using 400 gs (FTI400 group, n  = 26) or 600 gs FTI lesions (FTI600 group, n  = 24). The study endpoint was spontaneous or adenosine‐mediated recovery of transisthmus conduction, after a 20‐min waiting period. Results: The study endpoint occurred in five patients (19.2%) in group FTI400 and in four patients (16.7%) in group FTI600, p  = .81. First‐pass CTI block was similar in both groups (50% in FTI400 vs. 54.2% in FTI600, p  = .77). There were no differences in the total number of lesions, total ablation time, procedure time and fluoroscopy duration between the two groups. There were no major complications in any group. In the total population, patients not achieving first‐pass CTI block had significantly higher rate of acute CTI conduction recovery, compared to those with first‐pass block (29.2% vs. 7.7% respectively, p  = .048). Conclusions: CTI ablation using 600 gs FTI lesions is not associated with reduced spontaneous or adenosine‐mediated recurrence of transisthmus conduction, compared to 400 gs lesions.